2022
DOI: 10.1186/s12877-022-03721-0
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide handgrip strength values and factors associated with muscle weakness in older adults: findings from the Brazilian Longitudinal Study of Aging (ELSI-Brazil)

Abstract: Background Handgrip strength (HGS) is a simple, quick, inexpensive, and highly reliable method for the assessment of muscle strength in clinical practice and epidemiological studies. This study aimed at describing the HGS values by age group and sex in Brazilians aged 50 years and over, determining age group- and sex-specific cutoff points for muscle weakness, and investigating sociodemographic and anthropometric variables associated with muscle weakness for each sex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…An analysis of the Irish Longitudinal Study on Ageing, which employed hand grip strength only, found that overweight and obesity were associated with lower odds of probable sarcopenia [ 9 ]. Consistent with this, in the Brazilian Longitudinal Study of Ageing, obesity was inversely associated with hand grip strength [ 19 ]. Others similarly observed that a larger overall body mass, indicated by higher BMI, was associated with stronger hand grip strength [ 38 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…An analysis of the Irish Longitudinal Study on Ageing, which employed hand grip strength only, found that overweight and obesity were associated with lower odds of probable sarcopenia [ 9 ]. Consistent with this, in the Brazilian Longitudinal Study of Ageing, obesity was inversely associated with hand grip strength [ 19 ]. Others similarly observed that a larger overall body mass, indicated by higher BMI, was associated with stronger hand grip strength [ 38 ].…”
Section: Discussionsupporting
confidence: 66%
“…Previously, we reported that overweight and obesity were associated with lower odds of probable sarcopenia, which was assessed by hand grip strength only [ 9 ]. Similarly, an analysis from the Brazilian Longitudinal Study of Ageing (ELSI-Brazil) showed that BMI was inversely associated with muscle weakness measured by hand grip strength [ 19 ]. In contrast, others report an increased risk of sarcopenia/probable sarcopenia in older adults with obesity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…ELSI-Brazil therefore provides an opportunity to understand better the contribution of factors such as educational attainment, the household economic situation, health behaviors, and a range of health conditions-separately and in combination, on mortality, longevity, disability, and inequalities in each of these outcomes for a nationally representative sample of older adults. Future research can further advance the state-of-the-art by incorporating ELSI's mortality data (including specific causes of death) with measures of physical functioning, cognitive performance, metabolic and other biomarkers, and genomic analyses (Lima-Costa et al, 2022). The study's ultimate objective is to harness such research for promoting healthy aging among older Brazilians and to inform the overall provision and continuous quality improvement of health and social services essential to reaching this goal.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline sample comprised 10, 000 older adults (9412 participated), residing in 70 municipalities from all five Brazilian geographic regions. Details of the ELSI study (See http://elsi.cpqrr.fiocruz.br) have been described elsewhere (Lima-Costa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation